Food Label Reading Education "Makmin Detective" Improves Knowledge, Attitude, and Ability to Read Food Labels Among Adolescents - Dewi, Nikmah Utami; Fadjriah, Rasyika Nurul; Sakung, Jamaludin M Sakung; Patui, Nurhaya S Patui; Khairunnisaa, Khairunnisaa (Jurnal Abmas Negeri (JAGRI), 2025)
The increasing prevalence of degenerative diseases such as hypertension and diabetes in adolescents is a serious concern, mainly due to the consumption of foods high in sugar, salt, and fat (GGL) and the low habit of reading food labels. This community service activity aims to improve the knowledge, attitudes, and abilities of adolescents in reading food labels in an effort to prevent degenerative diseases. The education was conducted at MTSS Al-Hasanat, Sigi Regency, through “Detective Makmin” interactive media in the form of modules and wall magazines, accompanied by demonstrations and label reading practice competitions. Evaluation was carried out through pre-tests and post-tests on 24 students using instruments that had been tested for validity. The results of the paired t-test and Wilcoxon showed a significant increase in knowledge (p < 0,001), attitudes (p < 0,001), and the ability to read food labels (p < 0,001) after the intervention. The education provided was proven effective in improving adolescent nutritional literacy, especially in understanding the GGL content on food and beverage packaging. A participatory approach, the use of local media, and active student involvement played an important role in the success of the activity. Similar programs are recommended to be expanded to other schools with digital media development and parental involvement to strengthen long-term impact.